Development and validation of a high-performance liquid chromatography method for determination of ractopamine residue in pork samples by solid phase extraction and pre-column derivatization. (August 2015) - Ding, Guanglong; Li, Deguang; Qin, Jiao; Zhu, Juanli; Wang, Baitao; Geng, Qianqian; Guo, Mingcheng; Punyapitak, Darunee; Cao, Yongsong
Abstract: Ractopamine (RAC) has been approved as a feed additive for swine, cattle or turkey, and is likely to have residue in edible animal products and may pose a potential risk for consumer health. Therefore, it is essential to establish a method to detect the residue of RAC in animal products. This work presents a rapid and sensitive HPLC method for the determination of RAC in pork samples with pre-column derivatization. The RAC derivative was separated on a kromasil C18 column and detected at 284 nm with a UV detector. The detection capability (CCβ) was 0.078 μg g − 1 and the linearity was established over the concentration range of 0.15–100.0 μg g − 1 . The overall mean recovery in spike range of 0.2 μg g − 1 to 100 μg g − 1 was 89.9% with the overall mean relative standard deviation of 4.1%. This method can be used for the quantification of RAC in pork samples and help to establish adequate monitoring of the residue of RAC. Highlights: A sensitive HPLC method for the determination of RAC in pork samples with low CCβ Extraction of ractopamine residue by liquid/liquid extraction, SPE and derivatization Separation of ractopamine derivative with TFA as an ion-pairing reagent